2012
DOI: 10.2337/dc12-0180
|View full text |Cite
|
Sign up to set email alerts
|

Growth-Differentiation Factor 15 Predicts Worsening of Albuminuria in Patients With Type 2 Diabetes

Abstract: OBJECTIVEDevelopment of micro- or macroalbuminuria is associated with increased risk of cardiorenal complications, particularly in diabetes. For prevention of transition to micro- or macroalbuminuria, more accurate prediction markers on top of classical risk markers are needed. We studied a promising new marker, growth-differentiation factor (GDF)-15, to predict transition to increasing stage of albuminuria in type 2 diabetes mellitus (T2DM). In addition, we looked at the GDF-15 potential in nondiabetic subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 26 publications
3
38
0
Order By: Relevance
“…Glomerular and renal tubular interstitial injuries play the main role in the pathogenesis of diabetic nephropathy, and to diagnose this pathologic entity, several glomerular and tubular damage markers have been recently identified. Increased levels of these markers are supposed to indicate proximal tubular damage in the case of kidney injury molecule 1, neutrophil gelatinase–associated lipocalin, N ‐acetyl‐β‐ d ‐glucosaminidase, cystatin C, chitinase‐3–like protein 1, plasma growth differentiation factor 15 . These tubular damage markers have been extensively investigated in predicting the occurrence of acute kidney injury after various nephrotoxic insults, such as ischemia during cardiac surgery or sepsis .…”
Section: Biomarkers Associated With Renal Structural Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glomerular and renal tubular interstitial injuries play the main role in the pathogenesis of diabetic nephropathy, and to diagnose this pathologic entity, several glomerular and tubular damage markers have been recently identified. Increased levels of these markers are supposed to indicate proximal tubular damage in the case of kidney injury molecule 1, neutrophil gelatinase–associated lipocalin, N ‐acetyl‐β‐ d ‐glucosaminidase, cystatin C, chitinase‐3–like protein 1, plasma growth differentiation factor 15 . These tubular damage markers have been extensively investigated in predicting the occurrence of acute kidney injury after various nephrotoxic insults, such as ischemia during cardiac surgery or sepsis .…”
Section: Biomarkers Associated With Renal Structural Lesionsmentioning
confidence: 99%
“…Increased levels of these markers are supposed to indicate proximal tubular damage in the case of kidney injury molecule 1, neutrophil gelatinase-associated lipocalin, 71 N-acetyl-β-D-glucosaminidase, cystatin C, chitinase-3-like protein 1, 72 plasma growth differentiation factor 15. 73 These tubular damage markers have been extensively investigated in predicting the occurrence of acute kidney injury after various nephrotoxic insults, such as ischemia during cardiac surgery or sepsis. 49,[74][75][76] The most studied biomarkers associated with DN are listed in Table 1.…”
Section: Renal Tubular Acidosismentioning
confidence: 99%
“…Although measurements of GDF15 levels are technically not feasible in murine blood samples, several human studies (6,9,12,21) have shown increased GDF15 plasma levels in patients with T2DM. Therefore, to confirm the upregulation of GDF15 in the mouse model of T2DM, we measured GDF15 expression in white adipose tissue of db/ϩ and db/db mice by real-time PCR.…”
Section: Effect Of Genetic Deletion Of Gdf15 On the Development Of Enmentioning
confidence: 99%
“…T2DM in mice. As GDF15 levels are rather low in healthy mice, we also explored the effects of genetic deletion of GDF15 on vascular function in a model of T2DM, a condition associated with increased GDF15 levels (12). Five female db/ϩ mice (B6.Cg-Dock7mϩ/ϩ Lepr db/J, 7 wk of age), heterozygous for a leptin receptor mutation, were purchased from The Jackson Laboratories (Charles River, L'Arbresle, France).…”
Section: Animalsmentioning
confidence: 99%
“…In the future, , it is expected that the CRC biomarker panel would not only expand, but would be refined through elimination of biomarkers as further studies are performed using the VeraCode™ immunoassay methods presented here. For example, GDF15 is a stress-induced cytokine and in addition to CRC has been shown to be a biomarker for a variety of conditions such as heart disease (reviewed in (Wollert and Kempf, 2012)) and worsening albuminuria in patients with type 2 diabetes (Hellemons et al, 2012). …”
Section: Discussionmentioning
confidence: 99%